2009
DOI: 10.1002/lsm.20791
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of carboplatin, cytarabine, paclitaxel, vincristine, and low‐power laser irradiation on murine mesenchymal stem cells

Abstract: Low energy density of LPLI increases and high energy density of LPLI decreases the proliferation of mMSCs. Furthermore, LPLI can prevent or attenuate some drug's cytotoxicity and amplify others'. The result depends on the applied energy density, on the type and concentration of the cytostatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…De Villiers et al [21] Human adipose tissue 24, 48, and 72 h after irradiation The irradiated cell group had a statistically significant increase on cell proliferation at 24 and 72 h when compared to the nonirradiated group Horvat-Karajz et al [22] Murine bone marrow 24, 48, and 72 h after the first irradiation Biostimulation at lower doses in all time point evaluated and inhibition in cell growth after 48 h at higher doses (11.7 J/cm 2 ) Mvula et al [23] Human adipose tissue 24 and 48 h after irradiation Increase of cell proliferation in irradiated cells when compared to nonirradiated cells at the intervals of 24 and 48 h Ong et al [24] Human orbital fat tissues 24, 48, and 72 h after irradiation LED irradiation showed no effect on human orbital fat stem cells proliferation Soares et al [25] Human periodontal ligament 0, 24, 48, and 72 h after irradiation The dose of 1.0 J/cm 2 promoted a significant increase in cell proliferation at 48 and 72 h when compared to the control and the group that received a dose of 0.5 J/cm 2 Giannelli et al [26] Murine bone marrow 0, 24, 48, and 72 h after irradiation Cell proliferation was significantly higher at 72 h after irradiation compared to the control group Pereira et al [27] Healthy and inflamed human dental pulp 24, 48, 72, and 96 h after irradiation…”
Section: Discussionmentioning
confidence: 98%
“…De Villiers et al [21] Human adipose tissue 24, 48, and 72 h after irradiation The irradiated cell group had a statistically significant increase on cell proliferation at 24 and 72 h when compared to the nonirradiated group Horvat-Karajz et al [22] Murine bone marrow 24, 48, and 72 h after the first irradiation Biostimulation at lower doses in all time point evaluated and inhibition in cell growth after 48 h at higher doses (11.7 J/cm 2 ) Mvula et al [23] Human adipose tissue 24 and 48 h after irradiation Increase of cell proliferation in irradiated cells when compared to nonirradiated cells at the intervals of 24 and 48 h Ong et al [24] Human orbital fat tissues 24, 48, and 72 h after irradiation LED irradiation showed no effect on human orbital fat stem cells proliferation Soares et al [25] Human periodontal ligament 0, 24, 48, and 72 h after irradiation The dose of 1.0 J/cm 2 promoted a significant increase in cell proliferation at 48 and 72 h when compared to the control and the group that received a dose of 0.5 J/cm 2 Giannelli et al [26] Murine bone marrow 0, 24, 48, and 72 h after irradiation Cell proliferation was significantly higher at 72 h after irradiation compared to the control group Pereira et al [27] Healthy and inflamed human dental pulp 24, 48, 72, and 96 h after irradiation…”
Section: Discussionmentioning
confidence: 98%
“…At the cell-layer level, the power density measured using a power meter (Ophir Optronics, Jerusalem, Israel) was 6.67 mW/cm 2 . Because biostimulation after irradiation may continue for 48 h [22], the cultures were irradiated every other day since in half of them the medium had been changed to ODM. The first irradiation day was set as day 0.…”
Section: Irradiation Proceduresmentioning
confidence: 99%
“…The conditioning regimen is known to be able to damage not only the HSC but also the bone marrow (BM) microenvironment [5], [6]. It has been suggested that stromal damage caused by conditioning regimens or previous chemo-therapy treatments may have a profound influence on engraftment kinetics [10].…”
Section: Discussionmentioning
confidence: 99%
“…The conditioning regimen is toxic for both hematopoietic stem cells (HSC) and BM microenvironment [5], [6]. The latter is crucial to ensure normal hematopoietic engraftment after transplantation [7][9].…”
Section: Introductionmentioning
confidence: 99%